2022
DOI: 10.1088/1361-665x/aca12e
|View full text |Cite
|
Sign up to set email alerts
|

Role of charge carriers in long-term kinetics of polyurethane electroactuation

Abstract: Previous work has shown that dielectrophoretic body forces resulting from permittivity and conductivity heterogeneities only partially contribute to the overall electromechanical deformation of segmented polyurethanes (PUs). In this work, we studied the experimental kinetics and electric current of PU thin films over a long time period (1–105 s) for different applied electric fields. Then, we thoroughly analyzed the drift behavior of electric carriers and its macroscopic effect using simple modeling and numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…This result agrees well with our previous study on the long-term kinetics of PU, where a linear relationship was observed between current density and electric field below 8 MV/m. 19 It is clear that I middle and I last were obtained arbitrarily by turning off the voltage, and that these values could be lower if a longer step voltage was applied. Nevertheless, this figure quantifies the observation that the current response was rectangular (similar to the applied step voltage) at low voltage, but was more trapezoidal at high voltage.…”
Section: A Voltage Step Functionmentioning
confidence: 99%
See 4 more Smart Citations
“…This result agrees well with our previous study on the long-term kinetics of PU, where a linear relationship was observed between current density and electric field below 8 MV/m. 19 It is clear that I middle and I last were obtained arbitrarily by turning off the voltage, and that these values could be lower if a longer step voltage was applied. Nevertheless, this figure quantifies the observation that the current response was rectangular (similar to the applied step voltage) at low voltage, but was more trapezoidal at high voltage.…”
Section: A Voltage Step Functionmentioning
confidence: 99%
“…2, and the polymer conductivity σ can be estimated from the fitted line to reveal an electrical conductivity of σ = J/E 0 ≃ 2.7 × 10 −9 S/m, a value similar to the results of a prior investigation. 19 To analyze the effect of time on a PU sample under a high field, the step voltage was applied on a longer time scale. The plot in Fig.…”
Section: A Voltage Step Functionmentioning
confidence: 99%
See 3 more Smart Citations